THE ROLE OF FEEDBACK IN IMPROVING SPOKEN LANGUAGE PERFORMANCE - Teshaboyeva Nafisa Zubaydulla qizi; Ibragimova Shahrizoda Ravshan qizi (Ustozlar uchun, 2025)
Feedback plays a critical role in the development of spoken language skills. Whether provided by teachers, peers, or digital tools, effective feedback helps learners identify their strengths and areas for improvement, refine their pronunciation, and enhance fluency. This article explores various types of feedback—formative, corrective, peer-based, and technology-assisted—and how they contribute to better speaking performance in language learners. Focusing on the context of Uzbekistan, the study examines classroom practices, student responses, and the growing use of digital tools such as AI-based speaking apps and automated speech evaluation platforms. Drawing on both academic literature and local examples, the article shows that timely, specific, and constructive feedback improves learners’ self-awareness, confidence, and oral communication skills. It also discusses challenges such as emotional sensitivity, over-correction, and lack of individualization. Recommendations are provided for teachers, students, and institutions on how to integrate feedback effectively into speaking-focused lessons.